Optimal Trade-Off between Economic Activity and Health during an Epidemic - Tommy Andersson; Albin Erlanson; Daniel Spiro; Robert Östling (Lund University, School of Economics and Management, Department of Economics, 2020)
This paper considers a simple model where a social planner can influence the spread-intensity of an infection wave, and, consequently, also the economic activity and population health, through a single parameter. Population health is assumed to only be negatively affected when the number of simultaneously infected exceeds health care capacity. The main finding is that if (i) the planner attaches a positive weight on economic activity and (ii) it is more harmful for the economy to be locked down for longer than shorter time periods, then the optimal policy is to (weakly) exceed health care capacity at some time.
Keywords: E23; E27; E60; E65; 330; Covid-19 pandemic; SI-model; economic activity; health; optimal policy